Response of contrasting root genotypes of castor (Ricinus communis L.) to water stress: RESPONSE OF CONTRASTING ROOT GENOTYPES OF CASTOR TO WATER STRESS - P LAKSHMAMMA; LAKSHMI PRAYAGA; C SARADA (Journal of Oilseeds Research, 2016)
Two contrasting genotypes for root biomass i.e. RG-111 with good root, RG-1520 with poor root were studied for root, shoot growth till 90 DAS in root structures and also in field for seed yield by imposing water stress (30-90 DAS) during late rabi (2011-12). The reduction in root length was less due to stress. But root volume, dry weight and shoot growth reduced with stress and the per cent reduction was less in poorer root genotype (RG-1520) compared to good root genotype (RG-111). With drought stress in field, the growth before relieving stress, seed yield of different order branches and total seed yield reduced significantly in both genotypes. RG-1520 showed adaptation to survive drought stress in root structure and in field by increasing chlorophyll content (SCMR), less reduction in relative water content (RWC), decrease in specific leaf area (SLA) and increase in bloomcontent as that of good root genotype RG-111. But, seed yield reduction was more in poor root genotype (RG-1520) and also recorded high drought susceptibility index (DSI) as its photo assimilates were spent for its survival in stress and assimilate translocation was less for seed growth. Hence good root is important for crop survival, growth and seed yield especially in drought conditions.